Hypertrophic lichen planus versus prurigo nodularis: a dermoscopic perspective - Balachandra S. Ankad; Savitha L. Beergouder (Mattioli1885, 2016)
Background: Hypertrophic lichen planus (HLP) classically involves shin and ankles and is characterized by hyperkeratotic plaques and nodules. Prurigo nodularis (PN) is a chronic neurodermatitis that presents with intensely pruritic nodules. Histopathology of HLP and PN demonstrate epidermal hyperplasia, hypergranulosis, and compact hyperkeratosis. The dermis shows vertically arranged collagen fibers and an increased number of fibroblasts and capillaries in both conditions. Moreover, basal cell degeneration is confined to the tips of rete ridges, and band-like infiltration is conspicuously absent in HLP. Therefore, both conditions mimic each other clinically, which makes diagnosis difficult. Hence, there is a need for a diagnostic technique to differentiate both conditions. Objective: To evaluate dermoscopic patterns in HLP and PN and to study these patterns histopathologically. Materials and methods: The study was conducted at S. Nijalingappa Medical College in Bagalkot. It was an observational case series study. Ethical clearance and informed consent was obtained. A Dermlite 3 dermoscope (3Gen, San Juan Capistrano, CA, USA) attached to a Sony Cyber Shot camera DSC-W800 (Sony Electronics Inc., San Diego, California, USA) was employed. Histopathology was done to confirm the diagnosis. Results: There were 10 patients each with HLP and PN. HLP was seen in 8 males and 2 females. PN was observed in 7 females and 3 males. Dermoscopy of HLP demonstrated pearly white areas and peripheral striations (100%), gray-blue globules (60%), comedo-like openings (30%), red dots (40%), red globules (10%), brownish-black globules (30%), and yellowish structures (90%). In PN, red dots (70%), red globules (60%), and pearly white areas with peripheral striations (100%) were observed under dermoscopy. Conclusion: Both HLP and PN demonstrated specific dermoscopic patterns which can be demonstrated on histopathologic findings. The authors propose that these patterns are hallmarks of each condition. Thus, dermoscopy is a good diagnostic tool in the differentiation of HLP and PN.